Validasi Instrumen Social Provision Scale Pada Siswa Sekolah Menengah Atas: Studi dengan Penerapan Rasch Model - Deviana, Tina; Hayat, Bahrul; Suryadi, Bambang (Pusat Asesmen dan Pembelajaran, 2020)
The condition of Indonesia is currently being faced by the corona virus (COVID-19) pandemic 2019. The importance of solutions related to the existence of the role of teachers or educators to provide references such as social support to students in learning and teaching activities from home, this study conducted to provide research tools or instruments that can be used by educators or researchers by testing the validity of a social support construct (Social Provision Scale) measuring instrument using the Rasch Model. Although much has been done to test the validity of the Social Provision Scale, no one has examined it by involving social support in the context of Education. Likewise, the majority of research on social support uses confirmatory factor analysis, and no one has used the Rasch Model in validating the Social Provision Scale instrument, especially in Indonesia. The data used are secondary data from Putra of 326 people in SMA Negeri 29 South Jakarta using cluster sampling. The results of the application of the Rasch Rating Scale model show that the psychometric characteristics of the Social Provision Scale are very good and precise, as well as the compatibility of the items to the model. Implications and suggestions for future research are also discussed.